(untitled) (Research, Society and Development, 2021)
The success of endodontic treatment depends on knowledge of the internal dental anatomy. This article reports a rare case and the treatment of a maxillary first premolar with three separate roots. A 32-year-old female patient was referred for endodontic treatment of the upper right first premolar. On clinical examination, tooth #14 did not respond after the vitality test and radiographic examination revealed the presence of three roots. Patient underwent endodontic treatment. The knowledge of dental anatomy, as well as the possible variations, is of paramount importance for a general practitioner, through a diagnostic radiograph to have an idea of the tooth to be treated.